TIME-DEPENDENT FACTORS OF SOIL AND WEATHERING MANTLE DIVERSITY IN THE HUMID TROPICS AND SUBTROPICS: A CONCEPT OF SOIL SELF-DEVELOPMENT AND DENUDATION - Gracheva R.G.; Targulian V.O.; Zamotaev I.V. (My University, 2001)
Time-dependent processes are the most important factor contributing to diversity of the soil and weathering mantle (SWM) in the humid tropics and subtropics. Two models of SWM self-development in time are proposed and exemplified by soil chronosequences on tropical volcanic islands in the Pacific Ocean and in the humid subtropics on the east coast of the Black Sea. The first, derived from basic ash parent material lacking phyllosilicates, is an Eutric Regosol–Vitric Andosol–Mollic Andosol–Chromic Luvisol–Humic Ferralsol sequence. The second, formed on basic material rich in phyllosilicates, is a Leptosol/Regosol–Ferrallic Cambisol–Haplic Nitisol–Stagnic Acrisol sequence. Each component of these chronosequences contributes to SWM diversity in time and space and to the complexity of the soil cover patterns. The SWM denudation model is exemplified by a Stagnic Acrisol–Haplic Nitisol–Eutric Cambisol–Lithic Leptosol chronosequence on eroded hills and terraces of the east coast of the Black Sea. Temporal and spatial changes in soil properties (texture, chemistry, mineralogy) are examined in all three SWM chronosequences.